Analyzing Gender Representation in English Textbooks (IX & X) through Gender Schema Theory - Tiwari, Yasoda (Lumbini Journal of Language and Literature, 2024)
The current English textbooks of Nepal misrepresent gender in lexical, graphic, and symbolic ways. If a teaching material starts misrepresenting gender through an academic approach, It directly hits the mental and behavioural aspects of students. This study explores gender representation in the current English textbooks IX and X from the perspective of qualitative research design and the Gender Schema Theory and Critical Discourse Analysis to explore how gender is represented in terms of visibility, character attitudes, and gender stereotypes. The results indicate that these textbooks misrepresented gender differently, including profession, social roles, prioritizing male roles, and social space. This dominance reveals a persistent gender bias favoring men in various activities, such as becoming athletes, holding prestigious positions, and participating in sports. Despite this bias, gender stereotyping has significantly decreased compared to previous research, with some evidence of equality in responsibilities, activities, and pictorial representations. This study suggests contributing to raising gender awareness in education in order to maintain equity and equality in learning.